Effects of enzymatically treated Artemisia annua L. on growth performance and some blood parameters of broilers exposed to heat stress. (4th January 2017) - Wan, Xiaoli; Jiang, Luyi; Zhong, Haoran; Lu, Yufang; Zhang, Lili; Wang, Tian
Abstract: To evaluate the effects of enzymatically treated Artemisia annua L. (EA) on growth performance and some blood parameters of broilers exposed to heat stress (HS), 320 22‐day‐old Arbor Acres male broilers were randomly allotted into five groups with eight replicates of eight birds each. Broilers in the control group were housed at 22 ± 1°C and fed the basal diet. Broilers in the HS, HS‐EA0.75, HS‐EA1.00 and HS‐EA1.25 groups were reared under HS (34 ± 1°C for 8 h/day and 22 ± 1°C for 16 h/day), and fed basal diet with 0, 0.75, 1.00 and 1.25 g/kg EA, respectively. The experiment ended at 42 days. Dietary 1.00 and 1.25 g/kg EA decreased blood pH and elevated body weight gain, feed intake and carcass yield compared to the HS group. Broilers fed EA diets had lower serum concentrations of malondialdehyde and corticosterone and activities of alanine aminotransferase and aspartate aminotransferase, and higher serum total superoxide dismutase activity, tri‐iodothyronine concentration and tri‐iodothyronine/thyroxine than the HS group. Serum catalase activity in HS‐EA1.00 and HS‐EA1.25 groups and activity to inhibit hydroxyl in the HS‐EA1.00 group were higher than the HS group. In conclusion, dietary 0.75–1.25 g/kg EA addition alleviated HS induced impairments in broilers.